Implementasi model pembelajaran project-based learning untuk meningkatkan karakter toleransi dan peduli sosial siswa pada mata pelajaran pendidikan pancasila di kelas iv sekolah dasar - Nur Rohmawati; Chumdari Chumdari (Universitas Sebelas Maret, 2025)
This study aims to improve the character of tolerance and social care through the implementation of a project-based learning model in Pancasila Education lessons in the fourth-grade at Elementary School. This study used a qualitative research method based on Classroom Action Research (CAR) conducted in two cycles. The subjects of this study were fourth-grade students and teachers at Elementary School. The data collection techniques used were observation, interviews, and documentation, which were analysed using the Miles and Huberman model that also uses descriptive statistics. The implementation of the project-based learning model in cycle I obtained a percentage of 83% and in cycle II 95%. The percentage of tolerance character in cycle I was only 61% and increased to 86% in cycle II, while the social care character in cycle I showed a result of 53%, which increased to 85% in cycle II. Based on the research findings, it can be concluded that the implementation of the project-based learning model is effective in improving students’ tolerance and social care character.